2017
DOI: 10.1111/asj.12931
|View full text |Cite
|
Sign up to set email alerts
|

The use of accelerometer to measure sleeping posture of beef cows

Abstract: Sleep is one of the essential behaviors for mammals. The aims of this study were to validate the use of accelerometer for measuring sleeping posture of cattle. Duration of sleeping posture of seven Japanese Black cows from 19.00 to 07.00 hours was measured by both accelerometer and video, and a total of 67 accelerometer and video measurement sets were collected. We calculated Cohen's κ coefficient between accelerometer and video measurements and 91.5% of the κ-values were >0.80. Intra- and inter-observer coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…This outcome may be due to comfort level in different seasons, as multiple studies (Gomez & Cook, ; Ito et al, ; Tucker, Weary, & Fraser, ) have suggested that longer lying bout duration indicated greater comfort levels. Indeed, when pregnant Japanese black cows were moved into new tie‐stall sheds, they lied more frequent with shorter bout duration and slept less frequent with longer bout duration (Fukusawa et al, ). Thus, our observations here suggest that cows were less comfortable during summer under hot and humid condition.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This outcome may be due to comfort level in different seasons, as multiple studies (Gomez & Cook, ; Ito et al, ; Tucker, Weary, & Fraser, ) have suggested that longer lying bout duration indicated greater comfort levels. Indeed, when pregnant Japanese black cows were moved into new tie‐stall sheds, they lied more frequent with shorter bout duration and slept less frequent with longer bout duration (Fukusawa et al, ). Thus, our observations here suggest that cows were less comfortable during summer under hot and humid condition.…”
Section: Discussionmentioning
confidence: 99%
“…Five pregnant Holstein cows which milk in days were more than 90 days from each farm were arbitrarily selected at each season. The sleep posture of cow was measured 24 hr using an accelerometer (HOBO‐U12‐012, Onset, MA) fixed on the middle occipital with a halter (Fukasawa et al, ). All measurement started at noon.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…De Passillé et al (2010) and Ledgerwood et al (2010) fitted a three-axis accelerometer on the leg and classified the gait patterns (galloping, trotting, and walking) of calves and the lying/standing behaviors of dairy cows, respectively. Fukasawa et al (2018) measured the sleeping posture of cattle in lying positions by fitting a three-axis accelerometer on a halter on the middle occipital region. Mansbridge et al (2018) and Barwick et al (2018) classified the eating behaviors in sheep using a three-axis accelerometer worn on the ear.…”
Section: Introductionmentioning
confidence: 99%